1985
DOI: 10.1017/s0021859600056410
|View full text |Cite
|
Sign up to set email alerts
|

The influence of paclobutrazol on the distribution and utilization of 14C-labelled assimilate fixed at anthesis in oil-seed rape (Brassica napus L.)

Abstract: SUMMARYUntreated and paclobutrazol-treated field-grown plants of winter oil-seed rape cv. Jet Neuf were exposed to 14CO2 at anthesis. Redistribution of labelled assimilate was followed in sequential harvests between exposure and maturity.Labelled assimilates moved progressively from the leaves into the stem and reproductive parts. At maturity 9% of 14C fixed at anthesis had been mobilized into reproductive organs. Paclobutrazol increased the proportion of 14C translocated to the uppermost branches especially t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…During all three growth stages, leaves are the major sites for '''GO2 fixation and their contribution declined with plant age and the contribution of stem and pod walls to total ^"'GOz fixed by the plant increased with age. Our results are in agreement with the results of CHAPMAN et al (1984), BRAR and THIES (1977), INANGA et al (1979), ADO-QUAYE et al (1985) for oil seed rape. The reduction in '"^COi fixation by lower leaves was due to the onset of senescence in the lower leaves (GHAPMAN et al 1984).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…During all three growth stages, leaves are the major sites for '''GO2 fixation and their contribution declined with plant age and the contribution of stem and pod walls to total ^"'GOz fixed by the plant increased with age. Our results are in agreement with the results of CHAPMAN et al (1984), BRAR and THIES (1977), INANGA et al (1979), ADO-QUAYE et al (1985) for oil seed rape. The reduction in '"^COi fixation by lower leaves was due to the onset of senescence in the lower leaves (GHAPMAN et al 1984).…”
Section: Discussionsupporting
confidence: 94%
“…been studied in Brasslca napus and B. campestris (BRAR and THIES 1977, GHAPMAN et al 1984, FREYMAN et al 1973, MAJOR et al 1978, ADO-QuAYEet al 1985, 1986. However, in Brassica juncea the role of different parts in '•*GO2 fixation and photosynthate translocation had not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Stem DM was not altered because, although stem length was reduced, stem width was increased. Addo-Quaye et al (1985) also found that in oil seed rape (Brassica napus L.) paclobutrazol did not always reduce stem DM, even though stem length was significantlyreduced. The increase in root DM recorded in rape grown in soil with paclobutrazol residues was similar to that previously reported for sugar beet (laggard et al 1982), carrot , and perennial ryegrass (Hampton & Hebblethwaite 1985a).…”
Section: Discussionmentioning
confidence: 90%
“…For example, line 04C204 with the highest SOC potential had the lowest root to shoot ratio, indicating that this genetic line retains relatively more of its biomass in shoots rather than partitioning it to roots. Although line 04C204 had the lowest absolute amount of biomass accumulate among the four genotypes, the root to shoot ratios may be indicating that biomass partitioning among plant components is more important in determining SOC than the absolute amount of biomass accumulated (Addo-Quaye et al, 1985;Rood et al, 1984). This may be related to the fact that activity of key enzymes involved in triacylglycerol synthesis (e.g.…”
Section: Biomass Accumulationmentioning
confidence: 96%